Dypsis decaryi, Triangle Palm - Heather V. Quintana; Michael G. Andreu; Melissa H. Friedman; Mary McKenzie (EDIS, 2010)
FOR 240, a 2-page fact sheet by Heather V. Quintana, Michael G. Andreu, Melissa H. Friedman, and Mary McKenzie, describes this palm with a distinctive triangular shape to its trunk, which is endemic to the southeasternmost part of Madagascar and thrives in poor, dry soils—scientific and common names, description, allergen, and applications. Includes references. Published by the UF School of Forest Resources and Conservation, May 2010.